Muaragembong: Potensi alam dan olahan Dodol Pidada dalam video dokumenter - Sri Hapsari Wijayanti; Agnes Harnadi; Putra Putra; Toyomi Sayagiri; Aditha Thomas; William Frederich (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Not many people know the potential of Muaragembong Sub-District, Bekasi, West Java. The skills to process pidada mangroves, in particular, should be introduced to the people who also live in areas with the same mangrove forest wealth as Muaragembong. The purpose of this activity is to design a documentary video about the activities of a coastal woman who produces dodol pidada. The video, which titled